Tingkat Kepatuhan Minum Obat pada Pasien Hipertensi di Klinik Pratama Rawat Jalan (KPRJ) Mutiara Sehat Cinere Depok: Adherence Rate of Taking Medication in Hypertensive Patients at the Mutiara Sehat Cinere Depok Outpatient Primary Clinic (KPRJ) - Agung Fikri Pratama; Julia Totong; Imam Syafi’i (UIMA Press, 2025)
Hypertension has been widely known as a cardiovascular disease where people have above normal blood pressure. The disease is estimated to have caused a global increase in morbidity by 4.5%, and its prevalence is nearly as large as that in developed countries or in developing countries. The WHO estimates that around 1.13 billion people in the world suffer from hypertension, and this number is expected to increase annually to 1.5 billion people by 2025, with an estimated 10.44 million deaths from complications of hypertension and heart disease at a young age. To determine the level of adherence to taking antihypertensive drugs for patients with hypertension at the Mutiara Sehat Outpatient Primary Clinic (KPRJ), Cinere, Depok. This study uses a descriptive type of observation (Non-experimental) using a cross-sectional approach. Characteristics of female respondents (57%), age 45-54 (39.5%), last high school / vocational education (65.4%), and long suffering ≤ 5 years (74%). The adherence rate of taking medication for patients with hypertension at the Mutiara Sehat Outpatient Primary Clinic (KPRJ) in Depok is in the low category of 63%, the medium category of 27%, and the high category of 10%. The results showed that the adherence rate of taking medication for patients with hypertension was in the